Immersive communication and pro-environmental narratives: attention, comprehension, and empathy in the reception of VR and 2D films from the global south - Huamán-Huillca, Melissa (2026)
In the context of a global ecological crisis, virtual reality (VR) emerges as a narrative tool capable of transforming environmental communication. This study explores the comparative reception of two Latin American pro-environmental works —Hypha and Origen— in VR and 2D formats, using a qualitative approach with 37 Communication students in Peru. Through semi-structured interviews and non-participant observation, three key dimensions of the experience are analyzed: attention, comprehension, and empathy. Findings reveal that VR fosters embodied attention, forms of projected embodiment, and situated empathy with strong symbolic charge, whereas the 2D format supports critical distance, narrative clarity, and rational reflection. Moreover, the viewer’s profile —including age, gender, academic level, technological experience, and environmental interest— significantly influences the depth of the experience. From a Global South perspective, the study argues that immersive narratives should not be understood solely as technical solutions, but as ethical-aesthetic languages capable of activating sensitive forms of reconnection with the environment. As a multisensory and relational medium, VR must be considered through the lens of narrative agency, symbolic design, and the cultural disposition of the viewer. The study concludes that technological spectacle does not guarantee impact; rather, narrative coherence, symbolic inclusion, and ethical sensitivity are key to transformative storytelling.